AVO - Chopra, Satinder; Castagna, John Patrick (Society of Exploration Geophysicists, 2014)
AVO (SEG Investigations in Geophysics No. 16) by Satinder Chopra and John Castagna will provide readers with the most up-to-date knowledge on amplitude variation with offset. The book begins with a brief discussion on the basics of seismic-wave propagation as it relates to AVO, followed by a discussion of the rock-physics foundation for AVO analysis including the use of Gassmann's equations and fluid substitution. Then, the early seismic observations and how they led to the birth of AVO analysis are presented. The various approximations for the Zoeppritz equations are examined, and the assumptions and limitations of each approximation are clearly identified. A section on the factors that affect seismic amplitudes and a discussion of the processing considerations important for AVO analysis are included. A subsequent section explores the various techniques used in AVO interpretation. Finally, topics including the influence of anisotropy in AVO analysis, the use of AVO inversion, estimation of uncertainty in AVO analysis, converted-wave AVO, and the future of the AVO method are discussed.
Title from PDF title page (SEG eBooks Website, viewed 2015-01-30).
Keywords: Amplitude variation with offset analysis.; Seismology -- Mathematics.; Seismic reflection method.; Seismic prospecting.; elektronické knihy; electronic books